Performance of time based animation of physic motion - Loh, Ngiik Hoon (2012)
This study investigates the used of physics fonnula in achieving realistic time based animation. The needed of physics animation was to produce more realistic animations adhering to the basic laws of physics. According to the research, timing was an extremely important principle in animation. Timing gave meaning to the movement. To elaborate, the speed of an action defines how well the idea behind the action read to an audience. It could even bring to light the emotions hidden within the scen9 From the study, it seemed that creating realistic timing simulation in animation was significantly difficult particularly in setting keyframes. It was comprehensible that setting the value of keyframes was unambiguous whHe specifying the timing for keyframe was a harder task and often time consuming. The case study of bouncing balls' simulation was carried out and an algorithm was presented to produce physics-based real time simulation. Experiments had been carried out on different materials of the bouncing ball and different floor types. The fonnula created from this study was programmed into the software development platfonn. The results showed that the use of algorithmic fonnula achieved realistic-timing animation. Animation-based physics fonnula provided the animator the ability to control the realism of animation without setting the keyframe manually to achieve realistic-timing simulation.